2004
DOI: 10.1002/ardp.200400621
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Pure [1, 2‐Diamino‐1‐(4‐fluorophenyl)butane]platinum(II) Complexes: Synthesis and Antitumor Activity against MCF‐7 and MDA‐MB 231 Breast Cancer and LnCaP/FGC Prostate Cancer Cell Lines

Abstract: Germany b Laboratoire de ChimieEnantiomerically pure 1,2-diamino-1-(4-fluorophenyl)butanes were synthesized Pharmaceutique Organique, by stereoselective procedures. The enantiomeric purity was determined by 1 H Institut de Pharmacie, NMR spectroscopy after derivatization with (1R)-myrtenal. For the coordination Université Libre de Bruxelles, to platinum, the diamines were reacted with K 2 PtI 4 . Reaction with Ag 2 SO 4 Bruxelles, Belgium yielded the respective sulfatoplatinum(II) complexes, which were convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The same enantioselectivity was observed for the erythro compounds: (R,S)-4F-Ph/Et-PtCl 2 was more active than (S,R)-4F-Ph/Et-PtCl 2 . [11] The lack of enhancement of the cytotoxicity by elongation of the ethyl chain prompted us to investigate the influence of a branched isopropyl group at C2 on the antiproliferative effects. This structural modification only marginally affected the activity of the threo-configured complexes on the MCF-7 cell line ( Figure 2) but was of great significance for their effects on the MDA-MB 231 cell line (Figure 4).…”
Section: Structural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The same enantioselectivity was observed for the erythro compounds: (R,S)-4F-Ph/Et-PtCl 2 was more active than (S,R)-4F-Ph/Et-PtCl 2 . [11] The lack of enhancement of the cytotoxicity by elongation of the ethyl chain prompted us to investigate the influence of a branched isopropyl group at C2 on the antiproliferative effects. This structural modification only marginally affected the activity of the threo-configured complexes on the MCF-7 cell line ( Figure 2) but was of great significance for their effects on the MDA-MB 231 cell line (Figure 4).…”
Section: Structural Characterizationmentioning
confidence: 99%
“…[9] In an earlier study, we demonstrated the increase of in vitro cytotoxicity by the exchange of one 4-fluorophenyl residue with a methyl (4F-Ph/Me-PtCl 2 ), ethyl (4F-Ph/Et-PtCl 2 ) or propyl group (4F-Ph/ Prop-PtCl 2 ). [10][11][12] Interestingly, the C2-methyl substituent led to different cytotoxic effects of the threo isomers: S,S > R,R > S,R = R,S. [10] Elongation of the side chain in the erythro series with one or two methylene groups also produced this effect: &ok?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexes (labeled 4-10 in Fig. 1) have been synthesized using the methods we detailed previously (16)(17)(18)(19). Briefly, the diamines have been obtained starting from diversely substituted benzaldehyde derivatives and through the hydrocyanation of their corresponding imines followed by the reduction of the nitrile (21).…”
Section: Methodsmentioning
confidence: 99%
“…Our group has already synthesized various Pt(II) complexes structurally related to 1-phenyl-alkane-1,2-diamines (Fig. 1); those substituted by a fluorine atom at position 4 of the aromatic ring display significant anticancer activity in vitro (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%